The border event in the everyday: hope and constraints in the lives of young unaccompanied asylum seekers in Turkey. Issue 2 (25th January 2020) - Strasser, Sabine; Tibet, Eda Elif
ABSTRACT: This article addresses the everyday lives of young male migrants in a state care facility for unaccompanied minor asylum seekers in Istanbul, Turkey. We focus on how the EU-Turkey Statement, which came into force in March 2016, affected the young people's options and hopes and how they responded to the resultant strengthening of border control. Drawing on long-term ethnographic fieldwork in Istanbul and the Aegean area between 2015 and 2016 we show how this agreement became enmeshed with the young people's life trajectories during a period of increasing authoritarianism in Turkey. While current contributions to border studies in Turkey mainly discuss new strategies of joint border management, the border spectacle of the irregular corridor to Europe and emerging humanitarian interventions at the borders, this article traces how political and legal transformations of border control trickle down to the everyday of unaccompanied minors. We suggest analysing the EU–Turkey border regime in 2015/16 as a 'critical event' (Das [2007]. Life and Words: Violence and the Descent Into the Ordinary . Berkeley: University of California Press) and show how violence, exclusion and humanitarianism affect young men's lives.